The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1109/tasc.2003.812221
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metal powder addition on the structure and critical current of Ni-sheathed PIT MgB/sub 2/ tapes

Abstract: MgB 2 commercial powder was encased in a Ni tube and rolled into a monocore tape of about 5 mm in width and 0.3 mm in thickness. Different kinds of metal powder, i.e., In, Sn, Ag, Cu and Ni, were added to the MgB 2 core. Addition of the low melting point metal powder, e.g., In and Sn, has been found to enhance significantly the value in MgB 2 tapes. Annealing at a low temperature yields further increase in the of tapes with In and Sn addition. The enhancement in by the In addition and the low temperature annea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The wires were annealed at 873 K for 2 h in Ar atmosphere. The details of the specimen preparation are found in [5] and [9].…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The wires were annealed at 873 K for 2 h in Ar atmosphere. The details of the specimen preparation are found in [5] and [9].…”
Section: Samplesmentioning
confidence: 99%
“…The transport critical current density of the core in the PIT MgB 2 conductors depends on such parameters as the raw powder quality, sheath material, fabrication procedure, heat-treatment condition, and so on. In order to improve the critical current I c , the addition of metal powders, such as indium (In), to the MgB 2 core has been tried by some of the present authors [5,6]. Among them, it has been shown that 10 vol% In addition and annealing enhances I c by a factor of 6 to 7.…”
Section: Introductionmentioning
confidence: 99%
“…The trials for enhancement of H c2 and J c in MgB 2 have been performed in single crystal, bulk, wire and thin film [66][67][68][69][70][71][72][73][74]. Two bands in MgB 2 (p and s bands) take part in not only the superconducting gap but also H c2 and its anisotropy (H // ab, H // c).…”
Section: Applicationmentioning
confidence: 99%
“…The anisotropy in the B irr of MgB 2 with respect to the direction of applied field is also illustrated 4) . 14) .…”
Section: Figmentioning
confidence: 99%